Design, Synthesis and Biological Activity Evaluation of S-Substituted 1H-5-Mercapto-1,2,4-Triazole Derivatives as Antiproliferative Agents in Colorectal Cancer - Mioc, Marius; Avram, Sorin; Bercean, Vasile; Kurunczi, Ludovic; Ghiulai, Roxana M.; Oprean, Camelia; Coricovac, Dorina E.; Dehelean, Cristina; Mioc, Alexandra; Balan-Porcarasu, Mihaela; Tatu, Calin; Soica, Codruta (Frontiers in Chemistry, 2018)
A series of novel S-substituted 1H-3-R-5-mercapto-1,2,4-triazoles, obtained by docking based virtual screening (DBVS) of a previous constructed compound library, were synthesized and evaluated for their biological activities on a colorectal cancer cell line, HT-29. Among all synthesized compounds, TZ55.7, which was retained as a possible PDK1 (phospholipid-dependent kinase 1) inhibitor, exhibited the most significant cytotoxic activity against HT-29 tumor cell line. The same compound alongside other two, TZ53.7 and TZ3a.7, led to a significant cell cycle arrest in both sub G0/G1 and G0/G1 phase. This study provides future perspectives for the development of new agents containing the 1,2,4-mercapto triazole scaffold with antiproliferative activities in colorectal cancer.